Analisis Karakteristik Materi Fikih di Berbagai Jenjang Pendidikan Pada Kurikulum Merdeka - Amanda Trianita; Ahmad Reza Maulana; Mutiara Tsaniatus; Saepul Anwar; Abdul Fadhil (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to analyze the characteristics of fiqh material at various levels of education in the Merdeka Curriculum. The focus of the study lies on the pattern of material organization, depth of content, and relevance to the needs of students. The research method used is descriptive qualitative with a document analysis approach to textbooks, syllabi, and fiqh learning guides at the primary, junior high, and senior high levels. The results showed that the fiqh material in the Merdeka curriculum was designed progressively, starting from the introduction of basic concepts at the elementary school level, strengthening the application of worship at the junior high level, to enriching contemporary issues that require critical thinking skills at the senior high level. In addition, fiqh material at each level has been adjusted to the developmental stage of students and reflects the principles of flexibility and differentiation in learning. This study provides recommendations for optimizing the implementation of fiqh materials to make them more relevant to the challenges of the times and support the achievement of students' spiritual, social, and cognitive competencies in accordance with the vision of the Merdeka curriculum.